Design and Implementation of Canva-Based Digital Language Recognition Games to Enhance Early Childhood Cognitive Development at PG TK Cendekia Islamic School - Bela Anggreini Wahyu; Isti Rysdiyani (Universitas Cokroaminoto Palopo, 2026)
This study aims to design and implement Canva-based digital language recognition games to enhance early childhood cognitive development at PG TK Cendekia Islamic School. The research applies a simplified development approach involving 24 children aged 5-6 years, focusing on practical classroom implementation. The findings indicate that the integration of interactive digital games significantly improves children's cognitive abilities, particularly in language recognition, memory, and problem-solving skills, with the average cognitive score increasing from 65 in the pre-test to 85 in the post-test, a gain of 20 points (approximately 30.8%). The results demonstrate increased engagement, motivation, and learning outcomes, confirming that Canva-based educational games are effective tools for enhancing cognitive development in early childhood education.